Factors Inhibiting Incident Reportin Patient Safety - Fauzan, Ahmad; Felix Kasim; Rahmad Ramadhan Ritonga (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: RSUD dr. H. Kumpulan Pane (RSKP) has not yet successfully implemented real-time incident reporting as stipulated by the Minister of Health Regulation No. 11 of 2017. Objectives: Based on this situation, this study aims to analyze the condition of the patient safety incident reporting system in the inpatient unit at RSKP, identify the inhibiting factors, and propose priority policy alternatives to improve the system. Research method: To achieve these objectives, the Grounded Theory method, emphasizing qualitative data analysis from informants including structural officials, healthcare workers, and the quality and patient safety committee at RSKP, was used to reveal the conditions and inhibiting factors of patient safety incident reporting in the inpatient unit at RSKP. Meanwhile, to obtain priority alternatives for improving the incident reporting conditions, the researcher used the Analytical Hierarchy Process method. Results: The results of the study indicate several weaknesses in the reporting conditions, including very minimal incident reporting actions, incomplete implementation of system-oriented approaches, lack of coordination regarding assurance of immunity from punishment for incident reporting actions, unguaranteed independence from external parties, and partial patterns of patient safety incident resolution.  Conclusion: Patient safety incident reporting in the inpatient unit of RSKP remains suboptimal due to a weak reporting culture, insufficient training, unsupportive leadership, and an underdeveloped system. Strategic actions such as timely disbursement of service incentives, the establishment of a dedicated SPO improvement team, and the implementation of proportional sanctions are essential to enhance the overall quality of incident reporting.